2017
DOI: 10.1363/psrh.12024
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Abortion Care and Their Consequences For Patients Traveling for Services: Qualitative Findings from Two States

Abstract: CONTEXT Abortion availability and accessibility vary by state. Especially in areas where services are restricted or limited, some women travel to obtain abortion services in other states. Little is known about the experience of travel to obtain abortion. METHODS In January and February 2015, in-depth interviews were conducted with 29 patients seeking abortion services at six facilities in Michigan and New Mexico. Eligible women were 18 or older, spoke English, and had traveled either across state lines or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 29 publications
(70 reference statements)
6
120
0
3
Order By: Relevance
“…Our findings demonstrate that there are many reasons people in the United States may seek self‐managed medication abortion from online sources. The financial and logistical challenges those living in states with hostile abortion policies experienced when trying to access clinical care are consistent with those described in prior work examining the effects of restrictive abortion laws . However, those living in states with middle‐ground and supportive laws also experienced access barriers, including long distances to clinics, lack of transportation and difficulty finding information.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings demonstrate that there are many reasons people in the United States may seek self‐managed medication abortion from online sources. The financial and logistical challenges those living in states with hostile abortion policies experienced when trying to access clinical care are consistent with those described in prior work examining the effects of restrictive abortion laws . However, those living in states with middle‐ground and supportive laws also experienced access barriers, including long distances to clinics, lack of transportation and difficulty finding information.…”
Section: Discussionsupporting
confidence: 72%
“…Women who carry unintended pregnancies to term are more likely to enter prenatal care late and have fewer prenatal visits; they are more likely to smoke cigarettes, less likely to breastfeed their infants, or they breastfeed them for shorter lengths of time; and they may be at greater risk of maternal depression and anxiety than women who continue intended pregnancies. Unintended pregnancies that women decide not to carry to term lead to a need for abortion services, which are increasingly expensive and difficult to access …”
Section: Introductionmentioning
confidence: 99%
“…Unintended pregnancies that women decide not to carry to term lead to a need for abortion services, which are increasingly expensive and difficult to access. [7][8][9] Seventeen percent of women nationally experience more than one unintended pregnancy in their lifetimes. 10 There are few studies that examine how the resolution of an unintended pregnancy, whether in birth or abortion, affects the likelihood of having a subsequent unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…20 weeks) [8,9], instituting mandatory waiting periods [10,11], and restricting medication abortion [12,13]. Studies from several states have reported negative effects related to these laws and the subsequent reduced access, such as increased travel time, increased transportation and childcare costs, lost wages, the need to take time off of work or school, the need to disclose the abortion to more people than desired, and overall delays in care [10,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although women may not always know where to go for abortion care [15], they often use the internet to find abortion facility information [14]. Online searching for abortion information appears to be more prevalent in states with restrictive abortion laws and in those where abortion availability is limited, suggesting that women with reduced access to abortion are more likely to seek out information on abortion access online [16,17].…”
Section: Introductionmentioning
confidence: 99%